2016
DOI: 10.1016/j.jtemb.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury and brain development: A review of recent literature

Abstract: Methylmercury (MeHg) is a potent environmental pollutant, which elicits significant toxicity in humans. The central nervous system CNS) is the primary target of toxicity, and is particularly vulnerable during development. Maternal exposure to MeHg via consumption of fish and seafood can have irreversible effects on the neurobehavioral development of children, even in the absence of symptoms in the mother. It is well documented that developmental MeHg exposure may lead to neurological alterations, including cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(51 citation statements)
references
References 145 publications
2
49
0
Order By: Relevance
“…Similar results have been reported in animal models of brain development after exposure to MeHg in utero [8,9]. Moreover, extensive evidence has demonstrated that MeHg can lead to neural cell death, as well as to cytoarchitectural alterations in the nervous system [10,11,12,13,14]. There is an abundance of knowledge regarding reactive oxygen species (ROS) and especially effects of low-level MeHg exposure on cell cycle regulators in neural stem cells in vitro and in vivo [15,16,17].…”
Section: Introductionsupporting
confidence: 75%
“…Similar results have been reported in animal models of brain development after exposure to MeHg in utero [8,9]. Moreover, extensive evidence has demonstrated that MeHg can lead to neural cell death, as well as to cytoarchitectural alterations in the nervous system [10,11,12,13,14]. There is an abundance of knowledge regarding reactive oxygen species (ROS) and especially effects of low-level MeHg exposure on cell cycle regulators in neural stem cells in vitro and in vivo [15,16,17].…”
Section: Introductionsupporting
confidence: 75%
“…It is well known that ROS mediate MeHg-induced neurotoxicity in several experimental models, and mitochondrial changes may initiate a cascade of events culminating in cell death (apoptosis or necrosis) Bernardi et al, 1998;Kroemer and Reed, 2000;Yin et al, 2011). At present, several investigators reported that apoptosis occurs as result of organic Hg-mediated toxicity (dos Santos et al, 2016;Sokolowski et al, 2011;Ceccatelli et al, 2010), but the molecular mechanisms are not fully elucidated. Evidence indicates that Ca 2+ is linked to this neurotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Methylmercury (MeHg) is a global environmental contaminant targeting the central nervous system (CNS) (Farina and Aschner 2017;Santos et al 2016). Consumption of MeHg-containing fish products (Canuel et al 2006;Carrasco et al 2011;Steuerwald et al 2000;Stopford and Goldwater 1975) and rice (Rothenberg et al 2014;Zhang et al 2010) has been shown to induce neurodegeneration as well as be associated with neurodevelopmental disorders (Belletti et al 2002;Carocci et al 2014;Ceccatelli et al 2010).…”
Section: Introductionmentioning
confidence: 99%